Langage et pouvoir : effets du positionnement des idéologies étatiques dans la publicité cosmétique en Iran. Analyse discursive de la représentation de la femme dans les publicités anté- et postrévolutionnaires - Banafsheh Karamifar (Communiquer)
This article aims to examine the relationship between the political orientations and the rhetoric of advertisements during two different periods, pre- and post- Islamic revolution, in Iran. Based on samples of cosmetic advertisements printed during the last years of the first period and those of the second period, the study attempts to illustrate the fluctuation in linguistic strategies used in this genre for representing the Iranian women, who were forced to follow the governmental policies of their time. Adopting a textual analysis of the discourse approach as the methodological framework, the analysis of the corpus revealed, in particular, the change of thematic dispositions as well as an important enunciative and stylistic fluctuation from one period to the other in the advertisement texts, aiming at the construction of homogeneous national identities in a given time.